Effects of Monetary Incentives in Physician Groups: A Systematic Review of Reviews - Heider, Ann-Kathrin; Mang, Harald (Applied Health Economics and Health Policy, 2020)
Background Reimbursement systems that contribute to the cooperation and integration of providers have become increasingly important within the healthcare sector. Reimbursement systems not only serve as payment mechanisms but also provide control and incentive functions. Thus, the design of reimbursement systems is extremely important. Objectives The aims of this systematic review were to describe and gain a better understanding of the effects of monetary incentives in the setting of physician groups. Methods In January 2020, we searched the MEDLINE (PubMed), Cochrane Library, CINAHL, PsycINFO, EconLit, and ISI Web of Science databases as well as the gray literature and authors' personal collections. Results We included 21 reviews containing seven different incentive schemes/initiatives. The study settings and outcome measures varied considerably, as did the results within the incentive schemes and initiatives. However, we found positive effects on process quality for two types of incentives: pay-for-performance and accountable care organizations. The main limitations of this review were the variations in study settings and outcome measures of the studies included. Conclusions Monetary incentives in healthcare are often implemented as a control measure and are supposed to increase quality of care and reduce costs. The heterogeneity of the study results indicates that this is not always successful. The results reveal a need for research into the effects of monetary incentives in healthcare.
CRIS-Team WoS Importer:2020-04-10